Shoulder pain, health-related quality of life and physical function in community-dwelling older adults - Davis, Derik L.; Almardawi, Ranyah; Beamer, Brock A.; Ryan, Alice S.; Terrin, Michael L. (Frontiers in Aging, 2023)
The impact of shoulder pain on health-related quality of life and physical function among community-dwelling older adults (>60 years) not seeking medical care is not well understood. Forty-four community-dwelling older adult volunteers with low comorbidity were stratified into two groups by the presence (n = 18) or absence (n = 26) of shoulder pain. Participants completed the 36-Item Short Form and American Shoulder and Elbow Surgeon surveys and received shoulder range of motion and magnetic resonance imaging testing. Participants with shoulder pain perceived more difficulty accomplishing usual tasks secondary to their physical and emotion health and displayed inferior shoulder function, relative to participants without shoulder pain. This study suggests that shoulder pain reduces quality of life and physical function in the population of community-dwelling older adults not seeking medical evaluation for their symptoms.